Is it ethical for immunisations against human papillomavirus to be mandatory in young people aged 12–13 years old? - Frenki Gjika (Future Healthcare Journal)
The discussion surrounding the ethics of mandatory HPV vaccination for young adolescents aged 12–13 is complex. The human papillomavirus (HPV) is a prevalent sexually transmitted infection with certain strains linked to cervical and other types of cancers. While screening and behavioural interventions play important roles in prevention, vaccination has been shown to provide superior protection, thus reducing the incidence of HPV-related diseases by up to 90%.The effectiveness of the HPV vaccine, particularly Gardasil9, has led to discussions about making vaccination mandatory to improve public health outcomes. However, this raises ethical concerns about parental rights, individual autonomy and the implications of mandating vaccination in the context of sexual behaviour. This paper explores the ethical implications of a mandatory HPV vaccination programme, focusing on the ethical concerns of parental rights, gender equity and socioeconomic disparities. Additionally, the paper considers barriers to vaccination uptake and emphasises the importance of education and informed consent. It will be further discussed that while mandatory vaccination could lead to substantial public health benefits, it must be balanced by respecting individual freedoms and be accompanied by education campaigns. Ultimately, the ethical justification for mandatory HPV vaccination lies in its potential to prevent significant harm and promote health equity across populations.